2011
DOI: 10.3758/s13414-011-0136-4
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between memorized objects and abrupt onsets in oculomotor capture

Abstract: Recent evidence has been found for a source of task-irrelevant oculomotor capture (defined as when a salient event draws the eyes away from a primary task) that originates from working memory. An object memorized for a nonsearch task can capture the eyes during search. Here, an experiment was conducted that generated interactions between the presence of a memorized object (a colored disk) with the abrupt onset of a new object during visual search. The goal was to compare memory-driven oculomotor capture to ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We found that, despite instructions to maintain central fixation, the eyes were often captured by memory-match stimuli at the start of the retention interval (Figure 2), consistent with previous studies (Hollingworth et al, 2013;Hollingworth, Richard, & Luck, 2008;Mannan et al, 2010;Olivers et al, 2006;Silvis & Van der Stigchel, 2014;Wong & Peterson, 2011). However, this initial bias did not result in a sustained shift of attention as measured through pupillometry (Figure 3 and Figure 4); rather, later in time, attention appeared to be biased away from memory-match stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…We found that, despite instructions to maintain central fixation, the eyes were often captured by memory-match stimuli at the start of the retention interval (Figure 2), consistent with previous studies (Hollingworth et al, 2013;Hollingworth, Richard, & Luck, 2008;Mannan et al, 2010;Olivers et al, 2006;Silvis & Van der Stigchel, 2014;Wong & Peterson, 2011). However, this initial bias did not result in a sustained shift of attention as measured through pupillometry (Figure 3 and Figure 4); rather, later in time, attention appeared to be biased away from memory-match stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…Results show that remembering an object (e.g., a colored disk) can cause the eyes to make an involuntary saccade to that object if it appears in an unrelated search task (Olivers, Meijer, & Theeuwes, 2006). Additionally, the rate at which memorized objects capture the eyes is equal to or stronger than an abrupt onset (Wong & Peterson, 2011). Previous results demonstrating oculomotor capture involved salient environmental events, such as the abrupt onset of a new object or a change in object luminance.…”
mentioning
confidence: 73%
“…At the same time, a number of studies have shown that VWM content can bias even simple orienting saccades, when doing so is either irrelevant to, or even against task goals (Hollingworth et al, 2013;Mannan et al, 2010;Mathôt, Van Heusden, & Van der Stigchel, 2015;Olivers et al, 2006;Soto et al, 2005;Wong & Peterson, 2011). In these tasks observers remembered a color for a prospective memory test, while performing an eye movement-related task in between, in which either that target or a distractor could carry the memorized color.…”
Section: Discussionmentioning
confidence: 99%
“…In order to do so, the brain has to maintain some representation of what we are currently looking for. This representation, referred to as attentional template or search template, is thought to be activated in visual working memory (VWM; Carlisle, Arita, Pardo, & Woodman, 2011;Desimone & Duncan, 1995;Duncan & Humphreys, 1989;Hollingworth, Matsukura, & Luck, 2013;Mannan, Kennard, Potter, Pan, & Soto, 2010;Wong & Peterson, 2011), from which it guides selection of matching stimuli in the outside world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation